(untitled) (Scientific journal of the Fergana State University, 2024)
This article reveals the essence of the concept of digital technologies, their capabilities in education, their role in educational reforms in foreign countries, as well as the effectiveness of digital technologies in teaching activities. In addition, a scientific assessment of the issue is given by explaining the content of the concepts of digitalization, digital economy and digital technologies, and their definitions in dictionaries. An attempt was also made to reveal the scientific basis for the introduction of digital technologies into the educational process of our country and their use to demonstrate the professional activities of teachers.